PERAN BADAN RISET DAN INOVASI DAERAH (BRIDA) DALAM MENDUKUNG MINAT RISET PUBLIK DI KABUPATEN SUMENEP - Alfarisi Alfarisi; Nur Inna Alfiyah (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2026)
This study aims to determine the role of the Regional Research and Innovation Agency (BRIDA) of Sumenep Regency in supporting public research interest, as well as its impact on improving the quality and quantity of research in the region. This study uses a descriptive qualitative approach with data collection techniques such as interviews, observation, and documentation. Informants consisted of BRIDA representatives, academics, and other research practitioners. The research focus refers to the five main roles of the local government: regulator, dynamic agent, facilitator, innovator, and catalyst. The results show that BRIDA has played a strategic role in building a research ecosystem in Sumenep Regency through policy formulation, training, collaboration with universities, and facilitation of research and innovation based on local needs. BRIDA also encourages the active participation of civil servants, lecturers, students, and the community in research activities. However, challenges remain, particularly in efforts to acculturate a research culture to the non-academic community and in terms of budget and resource limitations. This study concludes that BRIDA is less than optimal in contributing significantly to generating public research interest and strengthening regional research governance. This role is crucial in supporting evidence-based policy and increasing regional competitiveness through relevant and sustainable innovation.Keywords : BRIDA, public research, regional innovation, government role, Sumenep Regency